Celiac Disease - Chai, Jianyuan (IntechOpen, 2021)
Celiac disease is a common autoimmune disorder triggered by eating gluten that affects at least 1% of the world's population. Despite many years of effort, its pathogenesis is still not understood completely. This book discusses several important aspects of celiac disease, including its primary contributor, the DQ2 gene. It also examines dysfunctional immune checkpoints, causes and treatments of refractory celiac disease, and the status of the gluten-free food market.